Prediction of the Location of Concealed Pluton on the Spatial Variation Characteristics of Volatile Matter in Coal Seams - Yihao Li; Jingui Zhao; Wensheng Li (Geofluids)
The lower the volatile value of coal, the higher the metamorphic degree of coal. As a vector, the spatial variation of the volatilization value of the coal seam be used to explore the location of concealed pluton and to characterize the maximum influence intensity of the magma thermal field. The eastern side of the Huyanshan intrusive pluton has amassed a large amount of C-P coal measurement and coal quality exploration data. The zonation distribution of coal seam volatile fraction data within the exploration area serves as an efficacious record of the intrusion process of the rock mass and a valuable resource for the exploration of the location of concealed plutons. Based on the data from 470 boreholes in the exploration area, contour maps of coal seams No. 02, No. 2, No. 6, No. 8, and No. 9; the true thickness contour maps of each coal layer; and the volatilizing profile map were created. The results indicate the following: (1) In the central region of the exploration area, from No. 9 to No. 8 to No. 6 to No. 2 to No. 02, the contours of volatiles in each coal seam exhibit a ring pattern, with the size of the ring and the size of the volatiles change regularly. This pattern strongly suggests that the concealed pluton is developed in the underlying layer of the coal seam. (2) According to the linear fitting of the relevant data, it is predicted that the concealed pluton is located at a depth of 65.4 m below the No. 9 coal seam. At a vertical distance of 159.1 m, the thermal field influence of the concealed pluton is lost, which aligns with the spatial distribution characteristics of volatiles in the coal seam as observed through drilling. (3) The occurrence of a significant interlayer slip between coal seam No. 6 and coal seam No. 2 in the overlying concealed pluton is indicated by the results of the hotspot migration analysis. The results are helpful to the search for magmatic-hydrothermal deposits and the exploration and development of coal and coalbed methane.